Assessing Renewable Energy Growth in the European Union - Romualdas Ginevičius; Gracjana Noga; Vladislavas Petraškevičius; Eigirdas Žemaitis; Miloslav Novotný (Energies)
As the world’s ecological situation worsens, the development of environmentally friendly renewable energy (RE) is becoming increasingly important. The main directions of scientific research devoted to the topic of RE are national socio-economic development of the country; development in the context of sustainable development; development policy and planning; evaluation of the achieved level of development; the situation in individual countries, etc. The analysis of literature sources conducted in this article shows that problems related to RE have not been sufficiently examined at the country or regional level, including in European Union (EU) countries. Such analysis helps to highlight regularities that are important for the further development of RE. The main purpose of this paper is to develop a comprehensive methodology for the quantitative assessment of RE development during the period under review and to validate it using the example of EU countries. The present research was conducted based on the methodology proposed in this article. In order to adequately assess the development of RE, it is necessary to rely on its scale and changes that occurred during the considered period (CP), i.e., to examine this development as a process. It is reflected by two parameters—the intensity of development and uniformity. The first is determined based on a value that assesses not the RE activeness at the end of the CP, but the general nature of the fluctuations that occurred during it. The uniformity of development is the sum of the ratios of its ideal and actual development values at the end of the time periods (years). The generalized RE development index is obtained by combining the values of the above parameters in an appropriate way. This helped to highlight the regularities and trends in the further development of RE: First, the level of economic development achieved by the country, measured by the gross domestic product per capita (correlation coefficient r = 0.7), has a significant influence on the development of RE. Second, on average, developed EU countries produce 52% of the RE from all electricity production, while for developing EU countries, the figure is 42%. Third, the development of RE is 1.7 times faster in developed EU countries compared to developing EU countries. Fourth, the country’s economic development has a significant influence on the development of RE in developing countries. Based on the research conducted, some contradictory results regarding the interaction between RE and countries’ economic development have been clarified. The practical benefit of the methodology is manifested in the following aspects: allows for the identification of factors that promote or hinder RE development; allows for the prediction of measures for further RE development. Thus, the methodology can serve as a methodological basis for the assessment and analysis of RE development in countries.